Rate of convergence of the price of European option on a market for which the jump of stock price is uniformly distributed over an interval - Mishura, Yu. S.; Soloveiko, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider a model of the market such that a jump of share price is uniformly distributed on some symmetric interval and establish the rate of convergence of fair prices of European options by using the theorem on asymptotic decompositions of distribution function for the sum of independent identically distributed random variables. We show that, in the prelimit model, there exists a martingale measure on the market such that the rate of convergence of prices of European options to the Black - Scholes price is of order 1/n 1/2.